Does Globalisation Have an Impact on Dual Banking System Productivity in Selected Southeast Asian Banking Industry? - Ribed Vianneca W. Jubilee; Fakarudin Kamarudin; Ahmed Razman Abdul Latiff; Hafezali Iqbal Hussain; Nazratul Aina Mohamad Anwar (Emerald Publishing Ltd, 2024)
Purpose – Globalisation has influenced many countries, over the last few decades with financial globalisation and liberalisation bringing regulatory reforms in the banking sector. Thus, this study aims to fill a gap in the literature by examining the influence of globalisation on Islamic and conventional bank productivity in Southeast Asia. Design/methodology/approach – The sample comprised 155 banks (23 Islamic and 132 conventional) from 4 countries from 2008 to 2017. Panel data techniques will be used, together with data envelopment analysis (DEA)-based Malmquist productivity index (MPI), to investigate the impact of chosen main determinants on bank productivity. A panel regression analysis will be performed after generating the productivity index from the DEA-based MPI frontier. Findings – According to the findings, Islamic banks are statistically significantly more productive than conventional banks, and the findings of the t-test are corroborated by the findings of nonparametric tests. Furthermore, the findings of the panel regression model reveal that bank specific factors and macroeconomic variables are significant determinants to bank productivity. Surprisingly, the findings also show that the influence of social globalisation elements tends to be negatively related to conventional bank productivity. Originality/value – This study adds to the existing literature by bridging the globalisation gap in the productivity of the dual banking industry, particularly in the specific context of Southeast Asia, given that the area is representative of Islamic and finance globally.